Theoretically Modified Optical Length Research on the Physical Boundary of the Double-Heterogeneous System - Lei, Lou; Xiaoming, Chai; Dong, Yao; Lianjie, Wang; Mancang, Li; Liang, Chen; Xiaoli, Liu; Hongbo, Zhang; Sinan, Li; Xiao, Tang; Nan, Zhou (Frontiers in Energy Research, 2022)
Because of the Double-Heterogeneity (DH), Dispersed particle-type systems cannot be described by traditional neutronic programs, and Volumetric Homogenization Method (VHM) will bring reactivity calculation deviation because of ignoring the spatial self-shielding effect of the particles. In this article, the relation betweenthe reactivity calculation deviation and the optical length of dispersed particle-type fuel and different types of burnable poisons is analyzed. And then it’s proposed that the influencing factors of reactivity calculation deviation can be integrated to a physical quantity named corrected optical length containing the above influencing factors.And the DH physical boundary is put forward that, when the corrected optical length is larger than 10-4, reactivity calculation deviation of VHM will be larger than 100pcm, and the DH of the dispersed particle-type systems should be considered.